Melatihkan Life Skills Melalui Pembelajaran Ipa Dengan Pendekatan Scientific Untuk Meningkatkan Hasil Belajar Siswa - Ummu Khairiyah (Universitas Islam Lamongan, 2017)
Abstract: Life skills are defined as psychosocial abilities for adaptive and positive behavior that enable individuals to deal effectively with demands and challenges of everyday life. Life skills are problem solving behavior used appropriately and responsibly in management of personal affairs. Life skills may be learn by teaching or simply by personal experience. Actually no life skills is used alone, there’s always a combination of more than more. Scientific approach is empirical knowledge. This approach can be considered as a way to think critically and systematically. The scientific method is rooted in the knowledge gained by finding problems through observation, experimentation, and through a process of objective reasoning and logic. Scientific approach strongly supports the active role of students in learning so that students can be learn life skills such as finding out, gather information, ask questions, and the establishment of confidence students through class discussions.Keywords: Life Skills, Pendekatan Scientific